Long-term sea-level projections with two versions of a global climate model of intermediate complexity and the corresponding changes in the Earth's gravity field - Makarynskyy, Oleg; Kuhn, Michael; Featherstone, Will (Pergamon, 2007)
Approximate estimations of future climate change can be produced by implementing numerical global climate models. In this study, versions 2.6 and 2.7 of the University of Victoria Earth System Climate Model (ESCM) were employed. Compared to other climatic projections, the novelty of this study consists in a significant extension of the projection period to the time-scale of 4200 years, and in comparisons of the results obtained with two sequential versions 2.6 and 2.7 of ESCM. Version 2.6 of ESCM couples the atmospheric, oceanic and ice processes. Version 2.7 of ESCM accounts for solar and ice-sheet forcing, as well as coupling land-vegetation-atmosphere-ocean carbon, and allows inclusion of ocean biology and dynamic vegetation modules. Our comparison exhibits essential quantitative and, moreover, qualitative differences in the parameters under consideration, which are surface air temperature, sea-ice and snow volumes, and surface pressure in a column of water averaged globally.The observed differences are attributed to the biological blocks added to ESCM version 2.7, changed numerics and explicit ice-sheet forcing. Furthermore, the non-steric sea-level change has been used to model corresponding gravity field changes (here in terms of geoid height) by evaluating Newton's volume integral and study the differences between the two software versions under consideration. In line with the model results, the estimated geoid height changes also exhibit a significant difference between the experiments' outcomes.